ASSESSMENT OF PSYCHO-SOCIAL IMPACT OF ACNE AMONG YOUNG ADULTS - A CROSS SECTIONAL STUDY AT A TERTIARY CARE HOSPITAL OF RAWALPINDI - Rashid, Zubaida; Mashhadi, Syed Fawad; Sharif, Imtenan; Zaidi, Syeda Urooj; Maroof, Saira; Khan, Mufliha; Liaqat, Umama (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the psychosocial impact of acne and to evaluate the quality of life in relation to severity of symptoms among young adults. Study Design: Cross-sectional – analytical study. Place and Duration of Study: Outpatient Department, Pak Emirates Military Hospital, Rawalpindi, from Sep 2018 to Feb 2019. Methodology: We included 300 individuals visiting the hospital and their quality of life was assessed using Acne quality of life Index questionnaire. Data was analyzed using SPSS-23. Results: Total scores were calculated for three domains of Quality of life in patients with Acne i.e. Self-perception, Emotional well-being and Social life. Out of these three domains, Social Life was most affected by acne (mean score 15.61 ± 7.37out of a total of 30) and Self-Perception was seen to be least affected (mean score 16.90 ± 8.20). There was a strong positive co-relation between the increasing severity of symptoms and impact on Self Perception (r=-0.58, p<0.01), between severity and Impact on Social life (r=-0.581, p<0.01) and between severity of symptoms and Impact on emotional well-being of the patients (r=-0.551, p<0.01). A significant difference was seen between the two genders with reference to the impact on “Social Life”, the mean score for Males being 13.96 ± 7.55 while that for Females being 17.29 ± 6.81 (p<0.01). Conclusion: Acne has significant impact on the quality of life of patients treated by primary care physicians. The severity of symptoms had strong positive correlation with self-perception, social and emotional domains.